Regional differences in antibiotic‐resistant pathogens in patients with pneumonia: Implications for clinicians. Issue 8 (4th August 2017) - Shindo, Yuichiro; Hasegawa, Yoshinori
ABSTRACT: Antibiotic resistance is of great concern for both infection control and the treatment of infectious diseases. Previous studies reported that the occurrence of drug‐resistant pathogens (DRPs)—for instance, methicillin‐resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa and extended‐spectrum β‐lactamase (ESBL)‐producing Enterobacteriaceae—were associated with inappropriate antibiotic treatment that resulted in adverse outcomes. In addition, unnecessary use of broad‐spectrum antibiotics for patients with non‐DRPs increased mortality. Therefore, the assessment of risk for DRPs at diagnosis is critical to avoid patients' adverse events. In the present review, we discuss regional differences in the prevalence of DRPs, which ranged from 6% to 45%, in patients with community‐onset pneumonia, including both community‐acquired and healthcare‐associated pneumonia. We then introduce the reported risk factors for DRPs in those patients, and present proposed prediction models for identifying patients with DRPs at diagnosis. Physicians should be aware that some of the risk factors for DRPs (e.g. prior antibiotic use and prior hospitalization) were common between regions; however, others may be different or the weighting of the risks may vary, even for the same risk factors. Therefore, a specific evaluation of risk factors for DRPs is recommended for each region and institution. Furthermore, we present a possible strategy for initial antibiotic selection in patients with community‐onset pneumonia, considering DRPs risk. We also discuss future directions for the study of DRPs in community‐onset, hospital‐acquired and ventilator‐associated pneumonia to improve the management of patients with pneumonia.